CIP contributes to policy discourse on accelerating economic growth and development for arid and semi-arid counties in Kenya - Awinoh, Martha (CGIAR System Organization, 2023)
The International Potato Center (CIP) participated in the 6th Kenya Institute for Public Policy Research and Analysis (KIPPRA) Annual Regional Conference held at Pwani University, Kilifi County from 21st to 23rd June. The conference brought together policy experts, stakeholders, youth, academia, policymakers, researchers, and development partners to discuss policy reforms, sustainable agriculture, infrastructure development, natural resource management, and digital innovation for unlocking the potential of Arid and Semi-Arid Lands (ASALs).